Strategic or communicative partnerships? Insights from sports programmes in the criminal justice sector. Issue 4 (2nd October 2021) - Morgan, Haydn; Baker, Colin
ABSTRACT: The concept of partnership working has gained traction as an alternative form of governance to address complex and multifaceted problems. The popularity of partnerships is also evident within the sport and physical activity sector, where their inclusion has become a staple of initiatives that utilise sport as a mechanism for development and to address social ills. This includes the issue of youth crime, where partnership working has become embedded as a key component of crime prevention and desistance strategies. While partnership working has become one of the most overused terms in contemporary policy, the failure to adequately grasp its meaning and to identify which aspects might usefully support it effectiveness is a long-standing problem. This paper adopts McDonald's (2005) theoretical framework, which draws a distinction between strategic and communicative partnerships, to examine the partnership workings of a UK organisation that seeks to build a better and safer society through the use of sport in the criminal justice system. Drawing upon qualitative data collected from the stakeholders of this organization (n=35), the paper presents insights into some of the tensions and challenges experienced by participants during the formation of operational partnerships and explores how these factors result in the development of either strategic partnerships, dominated by goal-attainment, instrumentalism and managerial authority; or communicative partnerships, where co-operation is central to the achievement of objectives.